Effects of losartan combined with exercise training in spontaneously hypertensive rats - Azevedo,L.F. (2003)
We investigate whether combined treatment with losartan, an angiotensin II receptor blocker, and exercise training (ET) in spontaneously hypertensive rats (SHR) would have an additive effect in reducing hypertension and improving baroreflex sensitivity when compared with losartan alone. Male SHR (8 weeks old) were assigned to 3 groups: sedentary placebo (SP, N = 16), sedentary under losartan treatment (SL, N = 11; 10 mg kg-1 day-1, by gavage), and ET under losartan treatment (TL, N = 10). ET was performed on a treadmill 5 days/week for 60 min at 50% of peak VO2, for 18 weeks. Blood pressure (BP) was measured with a catheter inserted into the carotid artery, and cardiac output with a microprobe placed around the ascending aorta. The baroreflex control of heart rate was assessed by administering increasing doses of phenylephrine and sodium nitroprusside (iv). Losartan significantly reduced mean BP (178 ± 16 vs 132 ± 12 mmHg) and left ventricular hypertrophy (2.9 ± 0.4 vs 2.5 ± 0.2 mg/g), and significantly increased baroreflex bradycardia and tachycardia sensitivity (1.0 ± 0.3 vs 1.7 ± 0.5 and 2.0 ± 0.7 vs 3.2 ± 1.7 bpm/mmHg, respectively) in SL compared with SP. However, losartan combined with ET had no additional effect on BP, baroreflex sensitivity or left ventricular hypertrophy when compared with losartan alone. In conclusion, losartan attenuates hypertension and improves baroreflex sensitivity in SHR. However, ET has no synergistic effect on BP in established hypertension when combined with losartan, at least at the dosage used in this investigation.